2019
DOI: 10.18632/aging.102414
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circGRAMD1B inhibits gastric cancer progression by sponging miR-130a-3p and regulating PTEN and p21 expression

Abstract: Circular RNAs (circRNAs) have emerged as essential regulators and biomarkers of various cancers. However, the effects of a novel circRNA termed circGRAMD1B in human gastric cancer (GC) remain unclear. A microarray was used to screen circRNA expression in GC. Quantitative real-time PCR was used to detect the expression of circGRAMD1B. Gain- and loss- of-function experiments were performed to investigate the biological functions of circGRAMD1B in vitro and vivo. Bioinformatics analysis, fluorescence in situ hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…23 For example, circGRAMD1B sponges miR-130a-3p to inhibit gastric cancer tumorigenesis. 29 In the present study, luciferase reporter assay indicated that miR-421 was a potential binding target of circEXOC6B. A research showed that downregulation of miR-421 inhibited the proliferation and migration of lung cancer cells.…”
Section: Discussionmentioning
confidence: 48%
“…23 For example, circGRAMD1B sponges miR-130a-3p to inhibit gastric cancer tumorigenesis. 29 In the present study, luciferase reporter assay indicated that miR-421 was a potential binding target of circEXOC6B. A research showed that downregulation of miR-421 inhibited the proliferation and migration of lung cancer cells.…”
Section: Discussionmentioning
confidence: 48%
“…Interestingly, we have found several circRNA-miRNA interactions that are capable of affecting the activity or expression of genes (e.g., PTEN, PI3K, AKT, p21 and PDK1) that are directly involved in PI3K/Akt pathway ( Table 2). For instance, circGRAMD1B/miR-130a-3p axis negatively regulates PTEN and p21, allowing higher proliferation, migration and invasion rates of GC cells [62]. Curiously, p21 is a cyclin/cdk inhibitor protein directly associated with the PI3K/Akt pathway [88].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the circRNAs we found may potentially promote gastric carcinogenesis by affecting mainly the PI3K/Akt pathway ( Figure 5A). ciRS-7↑/miR-7↓ [18] PTEN↓, PI3K↑ and pAkt↑ [18] Apoptosis inhibition, migration stimulus and poor clinicopathological and survival [18] circNRIP1↑/miR-149-5p↓ [27] AKT1↑ [27] Cell proliferation, migration and invasion and growth of tumor [27] circGRAMD1B↓/miR-130a-3p↑ [62] PTEN↓ and p21↓ [62] Cell proliferation, migration and invasion [62] circRNA0047905↑ [38] AKT1/CREB↑ [38] Cell proliferation and tumor progression [38] circMAN2B2↑/miR-145↓ [47] pPI3K↑ and pAkt ↑ [47] Cell growth and migration [47] hsa_circ_0008035↑/miR-375↓ [35] PDK1↑ * Increased of pAkt (Proliferation, migration and invasion) * circ-SERPINE2↑/miR-375↓ [36] PDK1↑ * circUBA1↑/miR-375↓ [37] PDK1↑ * Regarding the gastric cancer pathway (hsa05226), we noticed that it can be more affected by circNF1, circHIPK3, circPVT1 and circ_0000096, since they can regulate many target genes (Table S7). These circRNAs were also the most critical for other types of gastrointestinal tumors (Table S8).…”
Section: Discussionmentioning
confidence: 99%
“…CircFMN2 elevates expression of hTERT via sponging miR-1182 to promote cell proliferation in colorectal cancer [19]. CircRNA GRAMD1B inhibits gastric cancer cell proliferation, migration, and invasion via interaction with miR-130a-3p and regulation on PTEN and p21 expression [20]. In the present study, the interplays between circ-STAT3 and STAT3 as well as other downstream genes were also focused, which might provide a novel regulatory pathway for HB treatment.…”
Section: Introductionmentioning
confidence: 87%